Kemiskinan dalam Perspektif Fungsionalis (Studi Kasus Kampung Nelayan Cilincing) - Miftahul Fikri; Cahyo, Septian Dwi; Deviani, Nadya (Saskara : Indonesian Journal of Society Studies, 2023)
Reviewing the poverty that occurs in Cilincing Fishermen Village using a functionalist perspective, the author uses qualitative research methods as the main approach. Within the framework of qualitative methods, one of the techniques adopted is in-depth interviews. In depth interviews allow researchers to explore the perspectives and personal experiences of a number of residents who become research subjects. In the interview process, the participants had the opportunity to speak openly and deeply about their views on the poverty issue under study. Poverty that occurs provides indirect benefits for outsiders, such as being used as a place of research, providing assistance or funds, and other programs that support it. In a functionalist perspective, poverty does not always have to be eliminated, because with social stratification, the division of labor can be emphasized for the sake of the integrity of the social system in society. The existence of poverty will always exist, except when it has no function in society. This poverty can be minimized without eliminating its role.